The approach of portfolio matrix to assess efficiency of budget policy of Russia - I. I. Volkov (Plekhanov Russian University of Economics, 2018)
The article studies the issue of efficiency of federal budget expenses in Russia. To do that the authors propose to apply the approach of portfolio matrix of the state sector based on principles of the Boston matrix and the Ashridge matrix used in corporate finance. Within the frames of this approach key lines in budget policy expenses were analyzed that correspond to sections of the federal budget. For each of them basic services generated during using funds on separate lines in budget policy expenses were identified. It was found that in the structure of the federal budget expenses there are rather many lines, which form popular and needed for the population services that do not have a high quality. The authors suggest ways of raising efficiency of spending finance resources inside these lines at the expense of improving quality of such services. On this basis possible lines of raising efficiency of budget policy in Russia were identified, which show the potential of positive impact of the federal budget on business activity in Russia at the expense of higher satisfaction of customers with quality of state services. Provisions of this article can be used for designing recommendations for the federal budget within the frames of assessing economic expediency of its expenses’ structure.